Evaluation of anti-Listeria meat borne Lactobacillus for biofilm formation on selected abiotic surfaces - Pérez Ibarreche, Mariana (2014)
The ability of meat borne anti-Listeria Lactobacillus to form biofilms under different in vitro conditions and on abiotic surfaces was investigated. Biofilm formation by the adhesion to polystyrene microtiter plates was determined, this being higher for Lactobacillus curvatus CRL1532 and CRL705 and Lactobacillus sakei CRL1862. The physicochemical properties of the cell surface were relatively hydrophilic and acidic in character; L. sakei CRL1862 exhibiting the strongest autoaggregation. The adhesion of lactobacilli to stainless steel (SS) and polytetrafluoroethylene (PTFE) supports at 10 °C was found to be maximal for L. sakei CRL1862 on SS after 6 days. When biofilm architecture was characterized by epifluorescence and SEM, L. sakei CRL1862 homogeneously covered the SS surface while cell clusters were observed on PTFE; the extracellular polymeric substance matrix adapted to the topography and hydrophilic/hydrophobic characteristics of each material. The feasibility of L. sakei CRL1862 to form biofilm on materials used in meat processing highlights its potential as a control strategy for Listeria monocytogenes biofilms.